Rodent models of cholestatic liver disease: A practical guide for translational research. (23rd February 2021) - Gijbels, Eva; Pieters, Alanah; De Muynck, Kevin; Vinken, Mathieu; Devisscher, Lindsey
Abstract: Cholestatic liver disease denotes any situation associated with impaired bile flow concomitant with a noxious bile acid accumulation in the liver and/or systemic circulation. Cholestatic liver disease can be subdivided into different types according to its clinical phenotype, such as biliary atresia, drug‐induced cholestasis, gallstone liver disease, intrahepatic cholestasis of pregnancy, primary biliary cholangitis and primary sclerosing cholangitis. Considerable effort has been devoted to elucidating underlying mechanisms of cholestatic liver injuries and explore novel therapeutic and diagnostic strategies using animal models. Animal models employed according to their appropriate applicability domain herein play a crucial role. This review provides an overview of currently available in vivo animal models, fit‐for‐purpose in modelling different types of cholestatic liver diseases. Moreover, a practical guide and workflow is provided which can be used for translational research purposes, including all advantages and disadvantages of currently available in vivo animal models.